Kualitas Daging Babi dengan Pemberian Zeolit dan Tepung Darah Sebagai Sumber Protein dalam Ransum - P H Siagian; R Priyanto; R Sembiring (Faculty of Animal Science, Bogor Agricultural University, 2004)
Zeolite is a composite minerals from mining which can be used as a source of minerals in animal ration. It has high absorbability and cation exchange characteristics. This study was aimed to examine the influence of zeolit and blood meal in the pig ration on pork quality characterictics. The experiment used 27 crossbred pig comprising 19 gilts and 8 barrows, with initial weight of 25.29 + 2.67 kgs. They were set up in a completely randomized factorial design 3 x 3, where the first factor was zeolit levels (0, 3, and 6%) and the second factor was blood meal level (0, 5, and 10%). The results showed that there were no significant influence of zeolite, blood meal or their interaction on all meat quality characteristics including pH, water holding capacity, tenderness, color and intramuscular fat contents of pork, except the measurement at pH of six hours postmortem of the pork was significantly (P < 0.01) affected by blood meal level of the ration. Five percent (5%) blood meal in the ration gave the highest pH of pork compared to the other blood meal levels. Key words: pig, pork quality, zeolite, blood meal